2016
DOI: 10.1093/jb/mvw004
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of recombinant sugarcane sucrose phosphate synthase expressed inE. coliand insect Sf9 cells: an importance of the N-terminal domain for an allosteric regulatory property

Abstract: Sucrose phosphate synthase (SPS) catalyses the transfer of glycosyl group of uridine diphosphate glucose to fructose-6-phosphate to form sucrose-6-phosphate. Plant SPS plays a key role in photosynthetic carbon metabolisms, which activity is modulated by an allosteric activator glucose-6-phosphate (G6P). We produced recombinant sugarcane SPS using Escherichia coli and Sf9 insect cells to investigate its structure-function relationship. When expressed in E. coli, two forms of SPS with different sizes appeared; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
0
20
0
10
Order By: Relevance
“…Thus, it is postulated that the manipulation of sucrose transporter genes, as well as SWEET expression, in cooperation with increased SPS activity, might further increase sucrose concentration in the stalks of sugarcane. In addition, it was recently reported that N-terminal truncated SPS shows higher activity, avoiding regulation by allosteric effectors [42]. Future research will aim at further increasing sucrose accumulation in plants using the N-terminal deleted SPS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, it is postulated that the manipulation of sucrose transporter genes, as well as SWEET expression, in cooperation with increased SPS activity, might further increase sucrose concentration in the stalks of sugarcane. In addition, it was recently reported that N-terminal truncated SPS shows higher activity, avoiding regulation by allosteric effectors [42]. Future research will aim at further increasing sucrose accumulation in plants using the N-terminal deleted SPS.…”
Section: Discussionmentioning
confidence: 97%
“…SPS activity was assayed by measuring the formation of sucrose-6-phosphate in the desalted extract as previously described [42]. The assay mixture (70 µL) contained 30 mM MOPS-NaOH (pH 7.5), 10 mM MgCl 2 , 15 mM UDP-glucose, 10 mM fructose-6-phosphate (F6P), and 10 mM glucose-6-phosphate (G6P).…”
Section: Protein Extraction Enzyme Assay and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Untuk mempelajari peran domain N-terminus pada regulasi alosterik SPS, maka mutan SPS dengan pemotongan domain N-terminus dianalisis secara in vitro. Hasil analisis tersebut didapatkan bahwa SPS yang kehilangan domain N-terminus tidak dapat diaktivasi oleh G6P, tetapi spesifik aktifitas enzim meningkat hingga 10 kali lipat (Sawitri et al 2016). Meskipun mutan tersebut lebih stabil dan memiliki prospek dalam pengembangan bioteknologi, tetapi karakterisasi dan ekspresi penghilangan domain N-terminus SPS perlu dikaji lebih lanjut pada tanaman.…”
Section: Pendahuluanunclassified
“…Quantitatively, SPS activity was estimated by following Sawitri et al [23]. Leaf extract was cleaned up using Sephadex G-25 and subjected to an enzyme activity assay.…”
Section: Analysis Of Sucrose Phosphate Synthase Rubisco and Sucrosementioning
confidence: 99%